Experience and history: the reach and limits of phenomenological approaches to history - Grethlein, Jonas (History and theory, 2019)
Experience and History: Phenomenological Perspectives on the Historical World presents the summa of David Carr's phenomenological approach to history. I acknowledge the value of this perspective, but I find it doubtful that a phenomenological account can replace the paradigms - of memory and representation against which Carr pits it. The concept of historicity is, rather, complementary in that it alerts us to the prethematic presence of history. Phenomenologically, Carr's attempt to tie history closely to experience runs into problems as it is based on a questionable - use of Husserl's notion of retention and risks blurring the distinct temporality of history. At the same time, the central concepts of Carr's approach, both experience and narrative, could be deployed in further ways. As literary scholars have come to emphasize, narrative triggers experiences - in its readers. Thus, even if it is impossible to recreate the experiences of historical protagonists, narrative lends itself to giving readers a sense of the experiential dimension of the past. In this sense, narrative is not only a medium of representation, but also a means of presence.